Program Kampus Merdeka: Wadah Mahasiswa Berkreasi, Berinovasi, dan Berprestasi - Intan Defi Anggini; Masduki Asbari; Septiana Permata Noor (Journal of Information Systems and Management (JISMA), 2023)
The purpose of this study is to find out one of the programs from Merdeka Campus, namely the Certified Independent Internship and Study Program (MSIB) to Create a Container for Students to Create, Innovate, and Achieve. In this Study Report, it uses a descriptive qualitative method by listening to notes because the data sources are obtained by listening to oral narratives from the Directorate General of Diktiristek's Youtube channel entitled "Podcast Dikti Menyapa Ep.15". | The Independent Campus Program Creates a Container for Creative Students" presented by Ragah Samudera as a narrator and participant in the Certified Independent Internship and Study Program (MSIB) at Telkomsel Company and interviewed via podcast by Prof. Ir. Nizam, M.Sc., DIC., Ph.D (Acting Director General of Higher Education, Research and Technology). The results of this study explain that the government has provided a forum for students to be creative through Merdeka campus programs, one of which is the Internship Program and Independent and Certified Studies (MSIB). The Internship and Certified Independent Study (MSIB) Program at Merdeka Campus also aims to create opportunities for students to develop skills needed in the real world while still obtaining formal recognition in the form of a certificate. In addition, this